STUDI KEANEKARAGAMAN BIVALVIA DI EKOSISTEM PADANG LAMUN PANTAI PANDARATAN KECAMATAN SARUDIK KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Muhammad Fauzi; Ipanna Enggar Susetya (AQUACOASTMARINE, 2018)
Pandaratan Beach is a Beach located in Pondok Batu area, Sarudik Subdistrict, Tapanuli Tengah Regency which is an area that has seagrass beds with various roles in aquatic biota such as bivalves, where seagrass beds function as nurseries, as a place to search feeding ground, and areas to seek protection. The purpose of this study was to determine the bivalve diversity of seagrass beds at Padaratan Beach, carried out in March to April 2018 using purposive sampling method by taking and observing seagrass vegetation based on utilization. Data analysis included seagrass vegetation analysis, bivalve analysis, and water quality analysis. Found 2 types of seagrass with density at Station I 33.81%, Station II 20.27%, and Station III 25.38%. In bivalves 15 species were found at the study site. Bivalve Diversity Index at Station I 2.45, at Station II 2.48, and at Station III 2.43. Bivalvia uniformity index at Station I 0.91, at Station II 0.91, and at Station III 0.90. The bivalve dominance index at Station I was 0.07, at Station II 0.07, and at Station III 0.05. The relationship between seagrass density and density with bivalve diversity has a strong relationship, and shows that any increase in seagrass density affects the addition of bivalve species.Kata kunci: Bivalvia, lamun, keanekaragaman, pantai pandaratan.